Pengaruh Kompetensi Digital, Motivasi Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Dinas Komunikasi Dan Informatika Kabupaten Karawang - Iin Fatmawati; Sonny Hersona GW; Gusganda Suria Manda (Yayasan Riset dan Pengembangan Intelektual, 2025)
Improving the performance of government personnel has become a necessity amidst the growing demand for digitally based public services. The Department of Communication and Informatics of Karawang Regency plays a strategic role in driving the government’s digital transformation, making the organization's success highly dependent on employees’ digital competence, level of work motivation, and a work environment that supports task effectiveness. This study was conducted to analyze the extent of both partial and simultaneous influences of digital competence, work motivation, and work environment variables on employee performance. The research employed a quantitative approach with a descriptive-verificative method. The study population consisted of 100 employees of the Department of Communication and Informatics of Karawang Regency, all of whom were selected as samples using a saturated sampling technique. Data were collected through a questionnaire that had undergone validity and reliability testing, and subsequently analyzed using path analysis. The results indicate that digital competence, work motivation, work environment, and employee performance at the Department of Communication and Informatics of Karawang Regency fall into the good category, although each variable still presents its lowest indicator, namely content sharing for digital competence, personal commitment for work motivation, air ventilation for the work environment, and error minimization for employee performance. Furthermore, the influence analysis shows that digital competence contributes 7.37% to employee performance, work motivation contributes the highest influence at 33.32%, the work environment contributes 26.07%, and collectively, the three variables contribute 66.8%, while the remaining 33.2% is influenced by factors outside the scope of this study. Keywords: digital competence, work motivation, work environment, performance.